Modeling of Siltation at Bushehr Estuary by MIKE 21 - morteza Zanganeh; Aghil Hahmomeni (نشریه مهندسی دریا, 2016)
Estimation of siltation depth in harbors and estuaries plays an important role in design of marine structures. In this paper, siltation process at Bushehr estuary as one of the most important water bodies in south of Iran is modeled by so-called MIKE 21 mathematical model. To achieve this, at first a large scale hydrodynamic model calibrated by IRANSIAM registered water levels is developed while Chabahar registered tidal levels are considered as its boundary condition. Then, by developing a local model with fined mesh the dominant flow pattern is captured in the studied area. The local model is developed by hydrodynamic data taken from the large scale hydrodynamic model. Finally, via MIKE-21 MT module pattern of siltation in the study area is simulated by calibrating the model with sediment concentrations registered at Bushehr channel. Final results showed variation of siltation depth from 7cm in front of CPS platform till 22cm net siltation in front of Kosar platform inside the estuary.